Are Reference Rules Inessential to Meaning?. (3rd December 2020) - Ludwig, Kirk
This article responds to a case-based argument by Mark Richard that rule of reference is not essential to meaning. It objects that the argument requires shifting between understanding the relevant term in the case, 'marriage, ' as a determinable, in order to support one premise, and a determinate, in order to support another. On no univocal interpretation can both premises be made true.